Using mobile devices in the Bachelor of Nursing Sciences blended program at University of Nairobi : student perceptions and experiences - Bosire, Kefa O (Stellenbosch : Stellenbosch University, 2018)
Thesis (MPhil)--Stellenbosch University, 2018.